Ilamyyahi-yi tuzihi-yi mavazi'i idiuluzhik : (Guruhi Munsha'ab az Sazmani Chirikhai-yi Fada'i-yi Khalq)
An explanatory declaration on the ideological stance of the "group" split from "The Organization of the Iranian People's Guerrilla Freedom Fighters".